Cell migration and division in amoeboid-like fission yeast - Flor-Parra, Ignacio (The Company of Biologists, 2013)
Yeast cells are non-motile and are encased in a cell wall that supports high internal turgor pressure. The cell wall is also essential for cellular morphogenesis and cell division. Here, we report unexpected morphogenetic changes in a Schizosaccharomyces pombe mutant defective in cell wall biogenesis. These cells form dynamic cytoplasmic protrusions caused by internal turgor pressure and also exhibit amoeboid-like cell migration resulting from repeated protrusive cycles. The cytokinetic ring responsible for cell division in wild-type yeast often fails in these cells; however, they were still able to divide using a ring-independent alternative mechanism relying on extrusion of the cell body through a hole in the cell wall. This mechanism of cell division may resemble an ancestral mode of division in the absence of cytokinetic machinery. Our findings highlight how a single gene change can lead to the emergence of different modes of cell growth, migration and division.